STUDI LITERATUR: IMPLEMENTASI MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SEKOLAH DASAR - Ros Mawar Hutagaol, Kristina; Raharjo, Trijoko; Handoyo, Eko; Subali, Bambang; Avrilianda, Decky (Universitas Negeri Medan, 2025)
Abstract: Problem-based learning as a learning model that challenges students in analysis and critical thinking when facing problems related to the material being taught. This study aims to determine how the application of problem-based learning can improve elementary school students' mathematical problem-solving abilities. The method used in this study is the literature study method. A qualitative approach is applied in this study. Data collection was carried out through literature reflection, with a focus on searching for scientific articles that are relevant to the research context. After analyzing ten journal articles, it was found that the application of the problem-based learning model had a positive effect on improving mathematical problem-solving abilities at various levels of elementary school, both in lower and upper grades. The results of this study confirm that the use of problem-based learning can improve elementary school students' abilities in solving mathematical problems and has the potential to improve students' academic achievement Keyword: PBL, Problem Solving, Mathematics, Studi Literature Abstrak: Problem based learning sebagai model pembelajaran menantang siswa dalam analitis dan berpikir kritis saat menghadapi masalah terkait dengan materi yang diajarkan. Penelitian ini bertujuan untuk mengetahui bagaimana penerapan pembelajaran berbasis masalah dapat meningkatkan kemampuan pemecahan masalah matematika siswa SD. Metode yang digunakan dalam penelitian ini adalah metode studi pustaka. Pendekatan kualitatif diterapkan dalam penelitian ini. Pengumpulan data dilakukan melalui tinjauan literatur, dengan fokus pada penelusuran artikel-artikel ilmiah yang relevan dengan konteks penelitian. Setelah menganalisis sepuluh artikel jurnal, ditemukan bahwa penerapan model problem based learning memiliki pengaruh positif terhadap peningkatan kemampuan pemecahan masalah matematika di berbagai tingkatan sekolah dasar, baik itu di kelas rendah maupun di tingkat kelas tinggi. Hasil penelitian ini menegaskan bahwa penggunaan problem based learning dapat meningkatkan kemampuan siswa sekolah dasar dalam memecahkan masalah matematika dan berpotensi meningkatkan pencapaian akademik siswa. Kata Kunci: PBL, Pemecahan Masalah, Matematika, Studi Literatur